De la comparution à la décision pénale, le profil judiciaire de plus de 1 500 femmes - Fagnan, Andrée (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1992)
The Elizabeth Fry Society of Montreal conducted a study aimed at describing the judicial profile of women defendants from their appearance to their sentencing. This article presents the principal results of this study which concerns more than 1 500 women who appeared, in 1987, before the Quebec Criminal Court, at the Court houses at Montreal and Longueuil. Whether more than half these women are under 30 years of age, that they have never been charged before, that they are charged on one court only and of crimes against property, that they plead guilty and receive a probation order, very often the course of women through the judicial process is far from being linear. Once caught up in the system of judicial surveillance, there seems to be a sort of vicious circle established, where the system feeds the system, where the demeaning of the system becomes the offence that keeps these women within the system.